Pemahaman Kader PMII tentang Nilai-Nilai Pancasila untuk Meningkatkan Rasa Cinta Tanah Air - Sofyan, Fitri Silvia; Juantika Fahmi, Fani (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2023)
This study aims to determine the understanding of Indonesian Islamic Student Movement (PMII) cadres regarding the value of Pancasila in order to increase the love for the homeland in Karawang Regency and the PMII method in instilling Pancasila values in order to increase the love for the homeland in its cadres. The subjects of this research are PMII Karawang Cadres and PMII Karawang Branch Managers. The results of this study indicate that the understanding of PMII cadres regarding Pancasila values and love for the homeland can be said to be good with the existence of a clear regeneration module, which is stated in the organizational regulations and the PMII regeneration system which seriously internalizes the values of Pancasila to its cadres.